2018
DOI: 10.1002/nau.23529
|View full text |Cite
|
Sign up to set email alerts
|

The female continence mechanism measured by high resolution manometry: Urethral bulking versus midurethral sling

Abstract: Aims Traditional technology to characterize urethral pressure changes during dynamic conditions is limited by slow response times or artifact-inducing withdrawal maneuvers. The 8F high-resolution manometry (HRM) catheter (ManoScan™ ESO, Covidien) has advantages of fast response times and the ability to measure urethral pressures along the urethral length without withdrawal. Our objective was to determine static and dynamic maximum urethral closure pressures (MUCPs) and resting functional urethral length (FUL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Also, the impact of urethral support surgery and bulking injections on the urethral function has been reported. No statistically significant change was found in rest MUCP after retropubic and transobturator mid‐urethral slings and bulking agents 7–9 . If, as we show in this review, urethral failure is the dominant causal factor for SUI and operations do not change this, some incontinence would be expected postoperatively.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Also, the impact of urethral support surgery and bulking injections on the urethral function has been reported. No statistically significant change was found in rest MUCP after retropubic and transobturator mid‐urethral slings and bulking agents 7–9 . If, as we show in this review, urethral failure is the dominant causal factor for SUI and operations do not change this, some incontinence would be expected postoperatively.…”
Section: Introductionmentioning
confidence: 66%
“…No statistically significant change was found in rest MUCP after retropubic and transobturator midurethral slings and bulking agents. [7][8][9] If, as we show in this review, urethral failure is the dominant causal factor for SUI and operations do not change this, some incontinence would be expected postoperatively. This suggests that, in the absence of interventions targeting low urethral closure pressure, surgical results from support operations are bound to remain imperfect.…”
Section: Introductionmentioning
confidence: 76%
“…Further, 33 articles were reviewed and excluded because they did not satisfy the eligibility criteria. Nineteen studies concerning the efficacy and safety of UBAs for the treatment of SUI were included in this review: two of them were RCTs [9,10], while the other 17 studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] presented a prospective non-controlled or non-randomized design.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…It is important to understand the mechanism of urethral bulking in order to optimize the surgical technique and select the right patients. We were, therefore, attracted by the paper by Wasenda et al…”
mentioning
confidence: 99%
“…It is important to understand the mechanism of urethral bulking in order to optimize the surgical technique and select the right patients. We were, therefore, attracted by the paper by Wasenda et al 1 Wasenda et al's paper is the most recent in a series of studies with remarkable results based on the high-resolution manometry (HRM) catheter. We would like to comment on the following: 1) Test-retest reliability: In a previous study 2 the group has showed that the limit of agreement for Maximum Urethral Closure Pressure (MUCP) during dynamic conditions is ±40 cmH 2 O.…”
mentioning
confidence: 99%